PELAKSANAAN PENYALURAN ZAKAT OLEH BAITUL MAL ACEH SEBAGAI PENDAPATAN ASLI DAERAH DALAM UNDANG-UNDANG NOMOR 11 TAHUN 2006 TENTANG PEMERINTAHAN ACEH - Ristyana Tri Hastuti; Ahmad Redi (Jurnal Hukum Adigama, 2018)
Aceh is a province in Indonesia granted with a special authority to govern and manage its own government affairs. Among the special authorities is to include zakat into the locally-generated revenues. The provisions of zakat as locally-generated revenues are set out in Law No. 11 of 2006 on Aceh Government. The Baitul Maal is established by the Qanun to manage the zakat funds. The currently emerging issue is Article 10 of Governor Regulation No. 2015 stating that zakat can be distributed prior to the passage of APBA (Aceh local budget). The central issues are whether zakat can be distributed without passing through the APBA mechanism and what is the ideal arrangement for the zakat. The present study used the normative research method by utilizing secondary data supported by interviews. Results showed that the zakat funds could not be distributed prior to the approval of APBA since the officials in charge of it were reluctant to act accordingly.  Furthermore, zakat should ideally be regulated to be special  locally-generated revenues, rather than including it into the locally-generated revenues, in order not to delay its distribution.